Psicosis inducida ("foliex a deux") e intoxicación crónica por plomo. Reporte de un caso y discusión. - Arias, Jaime; Malaga, Germán (Revista Médica Herediana, 2013)
We report a case of two brothers suffering the same paranoia psychosis. The older one presented an altered consciousness and needed hospitalization. During hospitalization, he was considered as having lead chronic intoxication. The lead serum level was 65 ug/dl (N:<30 ug/dl) and the lead hair was 25 pg/gr-tiss (N:<10 pg/gr-tiss). He also presented clinically with encephalopathy, disorder of the autonomic dysfunction. He leaded his body for eleven years because of delutional ideas, and induced these ideas and behavior to his brother (folie a deux). The coincidence between these disorders in extremely rare so we believe this case report is of clinical interesting.